(untitled) (ENTHYMEMA, 2023)
This paper dives into some of the definitions of ekphrasis, from the classical ones to more innovative. Firstly, the research aims to broaden the definition of the technique. To do so, it separates the two main moments of the ekphrastic operation – ekphrasis as process and ekphrasis as text –, reading them as dispositifs. Secondly, the temporality of the ekphrastic dispositif is deepened, interpreting it as a form of integration between the processuality of the verbal sign and the simultaneity of the image. Finally, it looks at two Edoardo Sanguineti’s poetic ekphraseis – Reisebilder 14 and Cose 2 – that present a relevant temporal articulation, allowing us to observe how the simultaneity of the ekphrastic object and the processuality of the poetic text are integrated and made to collaborate.